2021
DOI: 10.33893/fer.20.2.532
|View full text |Cite
|
Sign up to set email alerts
|

Expected Impact of the Introduction of the Leverage Ratio at the Hungarian and EU Level

Abstract: From June 2021, a new set of mandatory requirements will enter into force in the European Union for all credit institutions registered in the EU, specifying in detail the method of calculating the leverage ratio and its minimum level. In this paper, we summarise the main criteria of leverage ratio regulation, the reasons for its introduction and the criticisms that have been expressed. We examine the likely impact of the new requirements as well as the types of credit institutions that may be most affected, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This cannot be carried out easily as risk-weighted capital adequacy requirements will prevent risk-taking. In addition, Kocsis and Seregdi's (2021) findings are similar to those of Acosta-Smith et al ( 2020) because these authors researched and focused on European banks.…”
Section: Basel III Leverage Ratiosupporting
confidence: 88%
See 3 more Smart Citations
“…This cannot be carried out easily as risk-weighted capital adequacy requirements will prevent risk-taking. In addition, Kocsis and Seregdi's (2021) findings are similar to those of Acosta-Smith et al ( 2020) because these authors researched and focused on European banks.…”
Section: Basel III Leverage Ratiosupporting
confidence: 88%
“…Also, Kocsis and Seregdi (2021) concluded that the introduction of a leverage ratio encourages banks to take higher risks in the EU but increased capital available from the leverage ratio can outweigh the negative effect and this is confirmed in the previous paragraph, as well. Moreover, raising new capital involves costs for banks and it is logical for banks themselves to invest in higher yielding but riskier assets (Kocsis and Seregdi 2021). This cannot be carried out easily as risk-weighted capital adequacy requirements will prevent risk-taking.…”
Section: Basel III Leverage Ratiomentioning
confidence: 53%
See 2 more Smart Citations